2021
DOI: 10.3389/fphar.2021.618844
|View full text |Cite
|
Sign up to set email alerts
|

How Aconiti Radix Cocta can Treat Gouty Arthritis Based on Systematic Pharmacology and UPLC-QTOF-MS/MS

Abstract: Background: Gouty arthritis (GA) is a common metabolic disease caused by a long-term disorder of purine metabolism and increased serum levels of uric acid. The processed product of dried root of Aconitum carmichaeli Debeaux (Aconiti Radix cocta, ARC) is used often in traditional Chinese medicine (TCM) to treat GA, but its specific active components and mechanism of action are not clear.Methods: First, we used ultra-performance liquid chromatography-quadrupole/time-of-flight tandem mass spectrometry to identify… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 63 publications
0
11
0
Order By: Relevance
“…The polyphenols of cultivated P. igniarius (CPP) were prepared in the same way as above. Furthermore, to elucidate the main active components in WPP and CPP better, UPLC-ESI-qTOF-MS, which is characterized by fast separation, high sensitivity, and accurate relative molecular mass calculation ( Ye et al, 2021 ), was used for identification. Surprisingly, similar active ingredients, such as protocatechuic aldehyde, hispidin, davallialactone, phelligridimer A, hypholomine B and inoscavin A, were identified in both WPP and CPP by UPLC-ESI-qTOF-MS. As members of the polyphenol family, the antioxidant and anti-inflammatory activities of protocatechuic aldehyde ( Chang et al, 2011 ), hispidin ( Jin et al, 2021 ), davallialactone ( Lee et al, 2008 ; Lee et al, 2011 ), phelligridimer A ( Wang et al, 2005b ), hypholomine B ( Shou et al, 2016 ) and inoscavin A ( Lee et al, 2006 ; Shou et al, 2016 ) have been widely reported.…”
Section: Discussionmentioning
confidence: 99%
“…The polyphenols of cultivated P. igniarius (CPP) were prepared in the same way as above. Furthermore, to elucidate the main active components in WPP and CPP better, UPLC-ESI-qTOF-MS, which is characterized by fast separation, high sensitivity, and accurate relative molecular mass calculation ( Ye et al, 2021 ), was used for identification. Surprisingly, similar active ingredients, such as protocatechuic aldehyde, hispidin, davallialactone, phelligridimer A, hypholomine B and inoscavin A, were identified in both WPP and CPP by UPLC-ESI-qTOF-MS. As members of the polyphenol family, the antioxidant and anti-inflammatory activities of protocatechuic aldehyde ( Chang et al, 2011 ), hispidin ( Jin et al, 2021 ), davallialactone ( Lee et al, 2008 ; Lee et al, 2011 ), phelligridimer A ( Wang et al, 2005b ), hypholomine B ( Shou et al, 2016 ) and inoscavin A ( Lee et al, 2006 ; Shou et al, 2016 ) have been widely reported.…”
Section: Discussionmentioning
confidence: 99%
“…Bioinformatics tools that are constantly updated provide new insights for drug development through high-throughput screening, targets prediction, and pathways enrichment. Traditional Chinese herbs have shown to be effective in treating joint disorders such as OA, RA [ 24 ], and gouty arthritis [ 25 ]; however, the key ingredients responsible for their therapeutic effects and underlying mechanisms by which their effects are manifested are still unknown. According to our bioinformatics results, Ginkgo biloba may exert anti-arthritic effects by inhibiting inflammatory cytokines such as IL-6 and modulating oxidative stress proteins such as hypoxia-inducible factor 1 subunit alpha (HIF-1α) and nuclear factor erythroid 2-related factor 2 (NFE2L2, NRF2).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the remaining 6 active compounds were also relatively easy to bind to the IL-1β receptor, and all had good affinities. Many studies showed that inhibition of PTGS2 (i.e., COX-2), NOS2, MAPK14, MMP9, MMP2, and activation of PPARG could improve inflammation in GA models, suggesting that these targets had potential importance in the pathogenesis of GA [45][46][47][48][49][50][51].…”
Section: Discussionmentioning
confidence: 99%